Indicators of land use by cattle: associations among methods and role of environmental factors - Costa, Mateus José Rodrigues Paranhos Da; Páscoa, Adriano Gomes; Sant’anna, Aline Cristina; Silva, Lívia Carolina Magalhães; Jung, Jens (Editora da Universidade Estadual de Maringá - EDUEM, 2017)
ABSTRACT. The objectives of this study were to investigate the associations among direct and indirect indicators of land use by cattle and to understand the role of some environmental factors on the definition of these indicators. The study was carried out in two areas, Nature Reserve (63.6 ha) and Private Area (30.4 ha), with 53 Hereford animals in each area. Daytime observations of animals’ location were used as direct indicator of land use; while cattle track and dung pat distributions throughout the areas were used as indirect indicators. Environmental characteristics recorded were: terrain slope, prevalence of woody vegetation cover (forests, isolated tress and open grasslands), as well as the position of fences, water sources and salt blocks. Spatial correlations among the three indicators of land use were low (r < 0.30). The environmental factors had lower predictive power of animals’ sightings distribution, followed by cattle tracks, and the highest predictive power occurred for dung pat distribution. We concluded that each one of the methods evaluated in this study addresses a different aspect of land use by cattle. The environmental factors assessed were useful to predict the dung pat distribution, but less valuable to predict the cattle tracks and animals’ sightings distributions.

RESUMO. Este estudo foi realizado para investigar as associações entre indicadores diretos e indiretos do uso do espaço por bovinos, além de avaliar o papel de algumas características ambientais na definição desses indicadores. O estudo foi conduzido em duas áreas, denominadas Nature Reserve (63,6 ha) e Private Area (30,4 ha), com 53 bovinos da raça Hereford em cada área. Observações comportamentais foram utilizadas como indicador direto do uso do espaço, enquanto as distribuições de trilhas feitas pelo gado e de placas de fezes foram utilizadas como indicadores indiretos. As características ambientais avaliadas foram: declividade, tipo de cobertura vegetal (florestas, pastagem com árvores isoladas, áreas abertas de pastagem), posição de cercas, fontes de água e sal. As correlações espaciais entre os três indicadores de uso do espaço foram baixas (r < 0,30). As características do ambiente tiveram baixo poder de predição da distribuição espacial dos animais, seguido pela distribuição das trilhas e maior para as placas de fezes. Concluímos que cada um dos métodos avaliados aborda um aspecto diferente do uso do espaço pelos bovinos. As características ambientais avaliadas foram úteis para predizer apenas a distribuição das placas de fezes, sendo menos úteis no caso das trilhas e observações diretas dos animais.
Indicadores de uso do espaço por bovinos: associação entre métodos e o papel de fatores ambientais
Keywords: beef cattle; tracks; dung pats; spatial statistical analysis; geographic information system; bovinos de corte; trilhas; placas de fezes; análise estatística espacial; sistema de informação geográfico